IZAR - User Guide - Ivanytska, Vitaliya; Sekničková, Jana; Kuncová, Martina, 1974-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
The goal of this paper is to explore a newly designed software support for solving multi-criteria decision-making problems -- IZAR, as well as to create a comprehensible manual for a common user interested in decision-making theory. IZAR is currently in a development stage; nevertheless, its available versions are already being used by operations research students. The first two sections of this thesis are focused on a brief introduction of all the solutions methods used in the current version of IZAR, while the third section is a practical user guide that includes examples of the problems and a comparative summary of different ways of their solution reached by the means of IZAR.
Vedoucí práce: Jana Sekničková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: matematické metody v ekonomii [obor bakal. práce]; bakalářské práce; bachelor's theses